Poker Player Behavior After Big Wins and Big Losses - Smith, Gary; Levere, Michael; Kurtzman, Robert (Management Science, 2009)
We find that experienced poker players typically change their style of play after winning or losing a big pot—most notably, playing less cautiously after a big loss, evidently hoping for lucky cards that will erase their loss. This finding is consistent with Kahneman and Tversky's (Kahneman, D., A. Tversky. 1979. Prospect theory: An analysis of decision under risk. Econometrica 47(2) 263–292) break-even hypothesis and suggests that when investors incur a large loss, it might be time to take a vacation or be monitored closely.